Cartel cases and the cartel enforcement process in the European Union 2001-2015: A quantitative assessment - Michael Hellwig; Kai Hüschelrath (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
We provide a comprehensive quantitative assessment of cartels and the related cartel enforcement process in the European Union (EU) from 2001 to 2015. In a first step, we present a detailed characterization of all cartel cases decided by the European Commission (EC) with respect to various criteria such as the number of involved firm groups, cartel market shares and market share asymmetries, involved industries, affected countries, types of infringement, types of cartel breakdown as well as cartel duration. In a second step, we complement this cartel-based analysis with a quantitative assessment of the public cartel enforcement process in the European Union - subdivided further into its duration, types of cartel detection, the leniency program, the settlement procedure, overall fines imposed, and the conclusive appeals process with the General Court (GC) and the European Court of Justice (ECJ).
urn:nbn:de:bsz:180-madoc-414932
Keywords: K21; L41; 330; Competition Policy; Cartels; Collusion; Enforcement; European Union